Diagnóstico de procedimientos de inspección estructural y propuesta de herramientas de estandarización. - Navarro-Mora, Ángel (Instituto Tecnológico de Costa Rica, 2014)
The structural inspection is a procedure that must be present during the construction of all civil works and is one of the most important to ensure the structural quality of the construction activities. This project was intended to determine if the construction sector need tools that standardize the structural inspection and generate tools that complement the professional judgment and experience of the inspectors, to ensure that no important criteria are ignored in the field and avoid any of the parties resulting directly or indirectly affected. To achieve the objectives a literature study was conducted, were investigated the rules and procedures of structural inspection, structural inspection visits were conducted at different projects and engineering professionals responsible of inspecting or responsible of building works was consulted through interviews and surveys. As a result, a diagnosis of the inspection procedures performed by different professionals and was obtained tools for inspecting structural elements of reinforced concrete and structural steel. Of this Work can be concluded that standardization tools are needed for structural inspection processes and tools are proposed to meet that need.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2014.
Keywords: Acero estructural; Construcción; Diseño; Normativa; Concreto reforzado